A Novel Strategy to Reverse General Anesthesia by Scavenging with the Acyclic Cucurbit[n]uril-type Molecular Container Calabadion 2. (August 2016) - Diaz-Gil, Daniel; Haerter, Friederike; Falcinelli, Shane; Ganapati, Shweta; Hettiarachchi, Gaya K.; Simons, Jeroen C. P.; Zhang, Ben; Grabitz, Stephanie D.; Moreno Duarte, Ingrid; Cotten, Joseph F.; Eikermann-Haerter, Katharina; Deng, Hao; et al.
Abstract : Background: Calabadion 2 is a new drug-encapsulating agent. In this study, the authors aim to assess its utility as an agent to reverse general anesthesia with etomidate and ketamine and facilitate recovery. Methods: To evaluate the effect of calabadion 2 on anesthesia recovery, the authors studied the response of rats to calabadion 2 after continuous and bolus intravenous etomidate or ketamine and bolus intramuscular ketamine administration. The authors measured electroencephalographic predictors of depth of anesthesia (burst suppression ratio and total electroencephalographic power), functional mobility impairment, blood pressure, and toxicity. Results: Calabadion 2 dose-dependently reverses the effects of ketamine and etomidate on electroencephalographic predictors of depth of anesthesia, as well as drug-induced hypotension, and shortens the time to recovery of righting reflex and functional mobility. Calabadion 2 displayed low cytotoxicity in MTS-3-(4, 5-dimethylthiazol-2-yl)-5-(3-carboxymethoxyphenyl)-2-(4-sulfophenyl)-2H-tetrazolium–based cell viability and adenylate kinase release cell necrosis assays, did not inhibit the human ether-à-go-go-related channel, and was not mutagenic (Ames test). On the basis of maximum tolerable dose and acceleration of righting reflex recovery, the authors calculated the therapeutic index of calabadion 2 in recovery as 16:1 (95% CI, 10 to 26:1) for the reversal of ketamine and 3:1 (95% CI, 2 to 5:1) for the reversal of etomidate. Conclusions: Calabadion 2 reverses etomidate and ketamine anesthesia in rats by chemical encapsulation at nontoxic concentrations. Abstract : The acyclic cucurbit[n]uril molecular container calabadion 2 dose-dependently decreased effects of ketamine and etomidate on electroencephalographic predictors of depth of anesthesia by encapsulation at nontoxic concentrations in rats. At doses sufficient to reverse neuromuscular blockade, calabadion 2 had minimal effects on anesthetic depth or duration. The effects of propofol and isoflurane were not reversed by calabadion 2.Supplemental Digital Content is available in the text.